Famtrip Diffable: An Inclusive Tourism Development as an Effort in Realizing Disability-Friendly Tourism - Wardana, Wisnu Febri; Herawan, Tutut (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2024)
In line with the urge for Inclusive Tourism Development, the tourism and hospitality industries have continuously faced a limited source of literacy on disability-friendly tourism. This is to achieve chance equality in the tourism sector. Other than facilities, inclusive tourism can be created and developed by creating a program or event. The program implemented can be designed to suit the needs of people with disabilities. “Fam trip Diffable” is one of the flagship programs organized by the Kulon Progo Regency Tourism Office to simultaneously publish or campaign for Inclusive Tourism Awareness which has been forgotten and abandoned and also educate people with disabilities in addition to traveling at the same time. Hence this paper aims to campaign the Disability-Friendly Tourism as one of the Inclusive Tourism Development movements that need to be considered. The “Famtrip Diffable” is one of the case studies in this qualitative approach research. With that, the Kulon Progo Regency Tourism Office can simultaneously promote the top tourist destinations in Kulon Progo Regency amid the pandemic. Considering this activity is carried out during the pandemic, of course, many things need to be considered such as health protocols and physical distance restrictions. Considering that this program involves many disabled friends ranging from deaf, mute, and blind people, this program is also designed to be able to adjust to the special needs of diffable friends. Such as collaborating with the Medical Team, Rescue, and Interpreter. Possible obstacles that may occur during the event can be prevented and overcome. This event also collaborates with Kompas TV in the Jalan-Jalan Lets Go” program which can expand publications, educate and inform the wider community about extraordinary programs by the Kulon Progo Regency Tourism Office. In summary, conclusions are drawn and some suggestions are offered regarding the topics that are likely to provide opportunities for future research directions.